Comparative study of Pelvi-calyceal system and relationship of structures at hilum of kidney between Nepalese and North Americans - Baral, P.; Koju, S.; Shrestha, R.; Kumar, S.; Baidya, R. (Journal of Gandaki Medical College-Nepal, 2019)
Introduction: Pelvi-calyceal system consists of renal pelvis along with major and minor calyces.The minor calyces unite with their neighbors two or three chambers to form the major calyces. The major calyces drain into the infundibula. The renal pelvis is formed from the junction of the infundibula. The common pattern of arrangement of structures at the renal hilum, antero-poteriorly is renal vein, renal artery and pelvis. Objectives: To compare the study of pelvi-calyceal system and relationship of structures at hilum of kidney between Nepalese and North Americans. Methodology: The gross and prosected kidney specimens were studied for pelvi-calyceal system and relationship of structures at hilum of kidney in Anatomy department. In Nepal, the study was undertaken in Gandaki Medical College, Kaski and in USA, it was done in Well-cornel University, New York. Result: Tricalyceal major calyx were found in 63.8% in Nepalese and Bicalyceal were found in 65.6% North Americans which is statistically significant variations. The number of minor calyces and pyramids varying 6 in Nepalese and 9 in North Americans were also statistically significant (p<0.05). The arrangement of structures at hilum of kidney from anterior to posterior(renal vein, artery and pelvis) in Nepalese and North American kidneys was 86.1% and 62.5% respectively whereas the structures arranged as renal artery, vein and pelvis from anterior to posterior was 13.9% and 37.5% . Conclusion: There are significant variations in pelvicalyceal system and relations of structures at hilum of kidneys of Nepalese and North-Americans.